"Waking us from this Endless Slumber": The Ottoman–Italian War and North Africa in the Ottoman Twentieth Century. (April 2019) - Hock, Stefan
The Ottoman–Italian War of 1911–1912, often overlooked as little more than a prelude to much greater calamities, produced a vibrant discourse in Ottoman-language newspapers that called attention to issues including the efficacy of international law, Ottoman sovereignty, and the place of North Africa in the Ottoman imperial imagination. This article explores the coverage of the war in the Ottoman-language press and argues that the outbreak of the Ottoman–Italian War produced similar claims on the need to protect the Ottoman nation – and Ottoman imperial ambitions – to those following the Balkan Wars to which historiography ascribes much more importance.